The Place of Mental Health Rhetoric Research (MHRR) in Rhetoric of Health and Medicine and Beyond - Molloy, Cathryn; Holladay, Drew; Melonçon, Lisa (University of Florida Press, 2020)
In sum, unlike some special issues that might be sort of “one off” engagements with interesting fringe topics, this is no “flash in the pan.” This special issue is, of course, imperfect since one issue cannot account for all of the work being done in the area. Instead, it offers notable examples of the range of topics and approaches that scholars are considering in this vibrant arm of RHM work. Readers can expect to see RHM continue to offer researchers in MHRR space to share their important work.